Actividad del (2E)-3-(2, 3-dimetoxifenil)-1-(4-metilfenil) prop-2-en-1-ona en presencia del poli(ácido maleico-co-2-vinil-pirrolidona) sobre un aislamiento clínico de Staphylococcus aureus productor de β-lactamasas (2012)
ABSTRACT: Due to the current problem of resistance to b-lactam antibiotics, it has become necessary, in search of a solution, to work with new molecules with pharmacological potential, and to use novel polymeric systems as matrices or pharmaceutical excipients. Objective: To evaluate the antibiotic activity of ampicillin combined with a synthetic chalcone-type compound, the (2E)-3-(2,3-dimethoxyphenyl)-1-(4- methylphenyl) prop-2-en-1-one, on a clinical isolate of penicillin-resistant Staphylococcus aureus in the presence of a water soluble polymer matrix known as poly(maleic acid-co-2-vinyl-pyrrolidone). Materials and methods: The synthetic compound and the polymeric matrix were obtained by previously described methods. Tests for antibiotic activity against the strain of penicillin-resistant Staphylococcus aureus were done by the broth dilution technique which provided the minimal inhibitory concentrations of the compounds tested. Results: The chalcone-ampicillin mix shows lesser antibiotic effect than the ampicillin-sulbactam used as referent. However, when such mix is combined with the polymer matrix, antibiotic activity significantly increases as evidenced by decrease in the minimal inhibitory concentration with respect to the ampicillin-sulbactam referent.